2016
DOI: 10.1007/s00167-016-4065-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of factor Xa inhibitors following opening-wedge high tibial osteotomy for venous thromboembolism prophylaxis

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
(50 reference statements)
0
14
1
Order By: Relevance
“…Although there are several studies regarding the incidence of VTE following TKA, 5,7,9,25 few studies have reported the incidence of VTE following HTO (►Table 6). 10,26,27 Some studies reported the incidence of VTE after lateral closed-wedge HTO (LCWHTO) in the Western population, which is higher than that observed in our study. It suggested that the prevalence of overall VTE after HTO was lower in Asians than in Westerners.…”
Section: Discussioncontrasting
confidence: 75%
“…Although there are several studies regarding the incidence of VTE following TKA, 5,7,9,25 few studies have reported the incidence of VTE following HTO (►Table 6). 10,26,27 Some studies reported the incidence of VTE after lateral closed-wedge HTO (LCWHTO) in the Western population, which is higher than that observed in our study. It suggested that the prevalence of overall VTE after HTO was lower in Asians than in Westerners.…”
Section: Discussioncontrasting
confidence: 75%
“…It has a sensitivity of 78% and specificity of 72% at a cut-off value of 53.5 ng/mL (Normal range 2.5 – 80 ng/mL). The area under the curve (AUC) on a receiver operating curve (ROC) range from 0.79 - 0.84 942,945,950,955,963,977,982 .…”
Section: - Are There Any Serological Biomarkers For the Diagnosis Of ...mentioning
confidence: 99%
“…It has a sensitivity ranging from 71% - 79% and a specificity of 27% - 41%. The AUC on a ROC is 0.82 944,945,950,959,960,966,981 .…”
Section: - Are There Any Serological Biomarkers For the Diagnosis Of ...mentioning
confidence: 99%
“…The incidence of pulmonary embolism (PE), as reported in three of the five studies. Sidhu et al, report a rate of 0.5%, Giuseffi et al, a rate of 1.1% and Kobayashi et al, reported PE rate of 6.3% in the edoxaban group and 16.7% in the non-edoxaban group 322,323,326 . None of the studies reported any VTE related complications such as death, bleeding, or others.…”
Section: - Is Routine Vte Prophylaxis Needed For Patients Undergoing ...mentioning
confidence: 97%
“…Kobayashi et al, performed a randomized controlled trial investigating DVT rates via venography following tibial osteotomy. The edoxaban (a factor Xa inhibitor) treated group had a rate of 16.7% compared to the non-edoxaban rate of 21.7% 326 . The incidence of pulmonary embolism (PE), as reported in three of the five studies.…”
Section: - Is Routine Vte Prophylaxis Needed For Patients Undergoing ...mentioning
confidence: 99%